Propuesta de disminución de tiempos muertos en máquinas CNC por medio de un modelo de mejores prácticas y la integración con una herramienta digital PLM - Jiménez-Vásquez, William (Instituto Tecnológico de Costa Rica, 2014)
Today, one of the biggest challenges for SMEs engaged in the production sector is finding a way to increase their income and expand their business without significantly increasing the template. SMEs are at a total disadvantage against companies of a larger size, which generally have greater financial support and more resources in general (employees, teams, contractors, suppliers) to carry out new initiatives. Almost all small manufacturers try to grow on their own and avoid falling into the temptation to attract the investment of venture capital companies for fear of losing control of their business. However, to maintain its independence and grow organically, SMEs must establish a business model that maximizes the use of resources and minimize costs. For this project, I studied the case of FEMA Industrial S.A., which is an SME dedicated to works of precision mechanics in the areas of maintenance of equipment, design and manufacture of products. In its facilities has several CNC machine tools, however, have not had the expected results in accordance with the investment represented. The advancement of technology and the development of numerical control CNC machines, has allowed the evolution of the manufacturing industry, progress incomplexity, time, and quality of products. The main problem of these teams is that they have a high cost, so for SMEs represents a considerable investment. This project is intended to identify procedures which can be improved to speed up time in CNC machines begin operations, looking for a maximum benefit from available resources. In addition, will seek to integrate part of a model with the best practices and procedures with a digital tool for the management of the life cycle of products or PLM, most with the aim to show the scope of the use of digital technologies to the benefit of the continuous improvement of the companies.
Proyecto de Graduación (Licenciatura en Ingeniería en Mecatrónica) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería en Mecatrónica, 2014.
Keywords: Análisis de procedimientos; Máquinas CNC; Sistemas CAD/CAM; Ciclo de vida del producto; Tecnología digital